In-situ detection of hydrogen evolution in a lubricated sliding pin on disk test under high vacuum. (January 2016) - Kuerten, Dominik; Winzer, Nicholas; Kailer, Andreas; Pfeiffer, Wulf; Spallek, Reiner; Scherge, Matthias
Abstract: In the present study the decomposition mechanisms of a multi-alkylated cyclopentane (MAC) lubricant on a steel surface were investigated in a ball-on-disk sliding test under vacuum. The lubricant was analyzed in-situ using a mass-spectrometer to study possible tribochemical reactions with the metal surface. The degradation of the lubricant was correlated with the formation of gaseous reaction products including hydrogen and various alkanes and alkenes. An increased carbon concentration was detected using XPS up to a depth of 1 µm below the surface of the wear track. This was attributed to reactions between the lubricant and the metal surface involving carbon chain cracking and fragmentation of the lubricant. An oxidation reaction between the lubricant and metal oxides was also identified. From the sliding test results it was shown that the rate of formation of gaseous reaction products increased with increasing load and sliding speed. Flash temperatures were calculated according to the Kuhlmann-Wilsdorf model. Finally, a correlation between the frictional power density and the evolution of hydrogen was established.